6(x+9)=3(8+3x)

Simple and best practice solution for 6(x+9)=3(8+3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+9)=3(8+3x) equation:


Simplifying
6(x + 9) = 3(8 + 3x)

Reorder the terms:
6(9 + x) = 3(8 + 3x)
(9 * 6 + x * 6) = 3(8 + 3x)
(54 + 6x) = 3(8 + 3x)
54 + 6x = (8 * 3 + 3x * 3)
54 + 6x = (24 + 9x)

Solving
54 + 6x = 24 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
54 + 6x + -9x = 24 + 9x + -9x

Combine like terms: 6x + -9x = -3x
54 + -3x = 24 + 9x + -9x

Combine like terms: 9x + -9x = 0
54 + -3x = 24 + 0
54 + -3x = 24

Add '-54' to each side of the equation.
54 + -54 + -3x = 24 + -54

Combine like terms: 54 + -54 = 0
0 + -3x = 24 + -54
-3x = 24 + -54

Combine like terms: 24 + -54 = -30
-3x = -30

Divide each side by '-3'.
x = 10

Simplifying
x = 10

See similar equations:

| 2/3p=10 | | 120=50 | | 3x=-14x | | 7a+84=7 | | 22x+6-24x=5-9 | | 3(y+5)+5y=7 | | -14r-6r-7r+-13=2 | | xsquared=324 | | 8=-4x+8(x-2) | | 3v^2-19v-40=0 | | 111-3x^2=0 | | 8+7x=4x+41 | | 20y-9y-4y+2y-8y=19 | | 2(2x-7)=7 | | 6x-5=7x+3 | | 119=7x-4(-4x+22) | | 2(v+2)-6v=24 | | 18x-7x-10x=2 | | 44(3+c)+c=c+4 | | p-p+p-p+4p=12 | | -30=4(u-8)-2u | | 5n+1p=1.06 | | sin^2x+2cosx=1 | | -3(u+5)=4u+48 | | x-0.13x=3500 | | -8u^2+28=0 | | 40x=61x | | 2x+3y+6z=360 | | 2/3(n−5/6)=21/2 | | 16x^5-44x^4+30x^3= | | 2x+63+7x+18=90 | | 3/4x=9/10 |

Equations solver categories